Bibliometric Analysis of Human Resource Development: Trends, Research Focuses, and Recent Developments - Darman; Loso Judijanto; Iwan Harsono; Alfa Santoso Budiwidjojo Putra (Westscience Press, 2023)
This bibliometric analysis delves into the dynamic landscape of Human Resource Development (HRD) research, exploring trends, collaborative networks, and influential works. Utilizing VOSviewer, we conducted a temporal analysis, co-authorship network analysis, keyword co-occurrence analysis, and citation analysis on a comprehensive dataset from leading databases. Temporal trends reveal an increasing scholarly interest in HRD since the early 2000s. Co-authorship networks unveil collaborative clusters, showcasing influential authors and fostering a collective research agenda. Keyword co-occurrence analysis uncovers interconnected thematic clusters, emphasizing the interdisciplinary nature of HRD. Citation analysis identifies pivotal works shaping HRD scholarship. Integrating these findings provides a holistic understanding of HRD research, offering implications for future endeavors and insights for scholars, practitioners, and policymakers.